neoliberal cultural Policy and Heavy Metal Music in the city Huanuco, Peru 1990 - 2010 - Yepes Aguirre, Jimmy Renzo (2013)
This study was designed to identify the benefits with the Hegelian method in the various aspects of politics and music in order to analyze their relationship. In this sense arose the following objectives: to determine the relationship between the Neoliberal Cultural Policy and heavy metal music, analyze its development and characteristics. It took the survey and interviews were applied to a nonrandom sample of 30 young (18 to 35 years old) metalheads of Huánuco. It identified three generations: Metalheads of the 1st Generation 1990 - 1996 (thesis); Metaheads of the 2nd Generation 1997 - 2003 (antithesis); Metalheads of the 3rd Generation 2004 - 2010 (synthesis). It shows the existence of a dialectical contradiction between heavy metal music (which is part of a subculture) and the dominant culture in the world (in this case the neoliberal cultural policy), both show a direct relationship not only in the chronological aspect but also on the ideological level.